How to GAN event unweighting - Backes, Mathias; Butter, Anja; Plehn, Tilman; Winterhalder, Ramon (SciPost physics, 2021)
SciPost Journals Publication Detail SciPost Phys. 10, 089 (2021) How to GAN Event Unweighting